Advanced Control of Wind Electric Pumping System for Isolated Areas Application - Mohamed Barara; Abderrahim Bennassar; Ahmed Abbou; Mohammed Akherraz; Badre Bossoufi (Institute of Advanced Engineering and Science, 2014)
The supply water in remote areas of windy region is one of most attractive application of wind energy conversion .This paper proposes an advanced controller suitable for wind-electric pump in isolated applications in order to have a desired debit from variation of reference speed of the pump also the control scheme of DC voltage of SIEG for feed the pump are presented under step change in wind speed. The simulation results showed a good performance of the global proposed control system.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6527